Helicobacter pylori‐negative extra‐nodal marginal zone B‐cell lymphoma of Mucosa‐Associated Lymphoid Tissue (MALT) type following Roux‐en‐Y Gastric Bypass (RYGB). Issue 1 (23rd January 2022) - Eagle, Zachary R.; Essien, Francis; Zibert, Kimberly; Miller, Charles; Van Dellen, Melissa; Eden, Rina; Pinson, Ross
Abstract: Gastric MALT lymphoma is a common type of non‐Hodgkin's lymphoma that has the potential for cure in patients found to have concomitant Helicobacter pylori ( H. pylori ) infection. This case report explores the evaluation, diagnosis, and treatment of H. pylori ‐negative MALT lymphoma in a patient with a history of a RYGB. Abstract : In patients with gastric MALT lymphoma and a RYGB, regardless of H. pylori status, surveillance of both the gastric pouch and remnant should be performed as it can occur in both locations despite anatomical separation.